1955
DOI: 10.1113/expphysiol.1955.sp001097
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Studies of Antagonists for 5‐hydroxytryptamine

Abstract: IN a previous paper [Gaddum and Hameed, 1954] we have summarized earlier work on antagonists for 5-hydroxytryptamine (HT) and described experiments with known drugs. The present paper gives the results of a study of the actions of a number of indole compounds in order to discover active antagonists. It was necessary to measure their potencies, and our attention was thus drawn to some of the difficulties which arise when antagonists are compared quantitatively with one another.Rough measurements may be made by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
144
0

Year Published

1956
1956
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(148 citation statements)
references
References 4 publications
4
144
0
Order By: Relevance
“…Most antagonists produce parallel rightward shifts of the angiotensin II concentration-response curve, without a ecting the maximal response. These are classi®ed as surmountable antagonists (Gaddum et al, 1955) and losartan is a typical example (Mochizuki et al, 1995). Insurmountable antagonists are able to depress the maximal response.…”
Section: Introductionmentioning
confidence: 99%
“…Most antagonists produce parallel rightward shifts of the angiotensin II concentration-response curve, without a ecting the maximal response. These are classi®ed as surmountable antagonists (Gaddum et al, 1955) and losartan is a typical example (Mochizuki et al, 1995). Insurmountable antagonists are able to depress the maximal response.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that an important action of 5-HT may be to modify the responses of tissues to other active substances. The effects on the rabbit's ear of 5-HT combined with various other drugs have been studied by Gaddum and Hameed (1954). The experiments described below are an extension of this work.…”
mentioning
confidence: 90%
“…Gaddum and Hameed (1954), and the cause of this discrepancy is unknown, but clear evidence of antagonism has now been consistently obtained in 6 experiments. It is possible that the preparation of ergometrine used by Gaddum and Hameed had become inactive.…”
Section: Ergometrinementioning
confidence: 99%
See 2 more Smart Citations